The structure and resilience of the European interbank market - Ivan Alves; Stijn Ferrari; Pietro Franchini; Jean-Cyprien Heam; Pavol Jurca; Sam Langfield; Sebastiano Laviola; Franka Liedorp; Antonio Sánchez; Santiago Tavolaro; Guillaume Vuillemey (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2013)
Financial institutions are connected to each other by a series of bilateral transactions. In normal times, institutions' connections may result in efficient risk transfer. But in crises, connections can facilitate contagion - as initial problems lead to chains of defaults and liquidity shortages - sparked by shocks which might arise within the financial system or from the real economy. Institutions are also interconnected in indirect ways, since they are exposed to common risk factors that can result in concurrent losses. For example, most banks extend loans secured by real estate: they are thus collectively exposed to falls in house prices. Resulting bank distress can then exacerbate initial problems: banks might simultaneously sell collateral (houses), thus worsening downward price spirals. Less tangibly, institutions can also be connected through perceptions of counterparties' creditworthiness. Given uncertainty, financial institutions may in general become reluctant to lend to each other and hoard liquidity. Potential for contagion due to interconnectedness is a key component of systemic risk. As a first step towards understanding the mechanisms of contagion, this paper abstracts from complex indirect connections between banks, and rather focuses on direct linkages between 53 large EU banks, based on unique data on interbank exposures collected by national regulators as of the end of 2011.
Keywords: G01; E58; G21; 330; interbank market; resilience; structure; contagion